P-C13 Impact of HIV status, HCV genotype, and number of DAAs on HCV viral kinetics in patients with HCV genotype 1 receiving DAA therapy. (March 2017) - Rosenthal, Elana; Bon, Dimitra; Kattakuzhy, Sarah; Tang, Lydia; Hermann, Eva; Kohli, Anita; Masur, Henry; Kottilil, Shyam; Wilson, Eleanor
Abstract : Background: A better understanding of the impact on HCV viral kinetics (VK) of HIV status, HCV genotype, and number of DAAs used may allow further optimization of DAA regimens. Methods: VK data was evaluated for studies of patients with HCV genotype 1 mono-infection treated with ledipasvir (LDV)/sofosbuvir (SOF) [SYNERGY A], LDV/SOF + GS-5885 [SYNERGY B], or LDV/SOF + GS-9451 [SYNERGY C]; and patients with HIV/HCV genotype 1 co-infection treated with LDV/SOF [ERADICATE], or asunaprevir (ASV) and daclatasvir (DCV) +/- beclabuvir (BCV) [CONQUER]. Viral kinetic modeling with a multiscale model was performed for all participants. Results: There was no statistically significant difference in the clearance rate of free virus (c), treatment effect (ε), and loss of infected hepatocytes (δ) when comparing HCV mono-infected and HIV/HCV co-infected patients treated with regimens containing 2 DAA, when comparing HCV patients to HIV/HCV patients treated with 3 DAA, or when comparing HIV/HCV patients treated with 2 DAA regimens vs. 3 DAA regimens. However, when comparing genotype 1a and genotype 1b infection in HIV/HCV co-infected patients treated with 2 DAA or 3 DAA regimens, a favorable treatment effect (ε) was identified in those with genotype 1a (p<0.001). Conclusions: HIV coinfection does not seem to affect HCV viral kinetics, while genotype 1a seems to have a rapid decline of HCV kinetics with multiple DAA therapy. HCV viral kinetics could be useful in individualized, response guided therapy in identifying patients who are likely to respond to a shorter duration of therapy.